PENGARUH KOMITMEN PROFESI, SIKAP KERJA DAN STRES KERJA TERHADAP KINERJA PEGAWAI BIDANG KEDOKTERAN DAN KESEHATAN KEPOLISIAN DAERAH SUMATERA UTARA - Lailatusy Syfa S.; Muhammad Caesar Akbar; Irfan Nurddi Syah; Betia Warassari; Aivan Saleh (Universitas Islam Sumatera Utara, 2020)
The Formulation of this research is how the professional commitment, work attitude, and occupational stress to the performance of Medical And Health Officers Of The North Sumatera Region Police, and the purpose of this research is to know and analyze the influence of professional commitment, work attitude, and occupational stress to the performance of Medical And Health Officers Of The North Sumatera Region Police. This research is a quantitative descriptive study. Data collection techniques are conducted through interviews, inquiry lists and documentation studies. The samples in this study were as many as 95 employees. Variables are measured at Likert scale. Hypothesis testing using multiple linear regression analyses through F-test and T-Test. The Results of the test in Unison showed that professional commitment, work attitude, and occupational stress demonstrated a very noticeable influence to the performance of Medical And Health Officers Of The North Sumatera Region Police, with the value Fcount 50,032 Ftable 2.70 and significance value of 0.000b. Adjusted number of R Square by 0. 610 or (61%) indicates that the percentage of contribution of independent variable influence (profession commitment, work attitude, and occupational stress) to the dependent variable (employee performance) was 61%. Partially, the commitment of the profession positively influence to the performance of Medical And Health Officers Of The North Sumatera Region Police with a value of tcount ttable (7,876 1,985) and a significance value of 0.000. Working attitude is positive and significant to the performance of Medical And Health Officers Of The North Sumatera Region Police, with the value tcount ttable (7,006 1,985) and significance value of 0. 00. Work stress is negatively and significantly affected by the performance of Medical And Health Officers Of The North Sumatera Region Police with a value of tcount ttable (-3,352 1,985) and the significance value of 0. 001. The highest value of a regression coefficient is a professional commitment (X1) of 0. 529 or 52.9% and is the most dominant variable affecting to the performance of Medical And Health Officers Of The North Sumatera Region Police.